Espetáculo teatral incêndios de Wajdi Mouawad e o estudo da relação entre teatro, memória e esquecimento - Mósca, Plínio (2015)
This Master’s dissertation consists of this work is to study the play Incendies (translated into English as Scorched by Linda Gaboriau) by Canadian playwright Wajdi Mouawad, who was born in Lebanon. One can see how the theme of the play relates to memory and forgetfulness when approaching to individual's memory whose origin is on the trauma of violent acts suffered by the main character: losing her son's father, losing her first son, being arrested, being raped, losing her twin children who were born inside prision. This series of violent acts generates memory ties, and the play reveals that this mother leaves the desire to undo these ties as her will. My analysis is based on theories by Maurice Halbwachs (2006) and Michael Pollak (1989) in order to deepen the discussion on memory, and on Raymond Williams (2002) and Peter Szondi (2004) for the analysis of the tragical sense in theater. As the research final product, my goal is to present a scene of the play (of approximately fifteen minutes), where the trial of the accused of war crimes on international court of justice. In this scene, Nawal, the mother, finds out that her rapist and her torturer is also her first son and father of her twin children.